When Temporal Orbits Collide: Embodied Trans Temporalities in U.S. Prisons. (March 2017) - Rosenberg, Rae
Abstract : This paper explores trans temporalities through the experiences of incarcerated trans feminine persons in the United States. The Prison Industrial Complex (PIC) has received increased attention for its disproportionate containment of trans feminine persons, notably trans women of colour. As a system of domination and control, the PIC uses disciplinary and heteronormative time to dominate the bodies and identities of transgender prisoners by limiting the ways in which they can express and experience their identified and embodied genders. By analyzing three case studies from my research with incarcerated trans feminine persons, this paper illustrates how temporality is complexly woven through trans feminine prisoners' experiences of transitioning in the PIC. For incarcerated trans feminine persons, the interruption, refusal, or permission of transitioning in the PIC invites several gendered pasts into a body's present and places these temporalities in conversation with varying futures as the body's potential. Analyzing trans temporalities reveals time as layered through gender, inviting multiple pasts and futures to circulate around and through the body's present in ways that can be both harmful to, and necessary for, the assertion and survival of trans feminine identities in the PIC.